Perspective of Internal and External Auditors of supply chain management Effects in Opportunities, Pressure and Capabilities for Fraud Risk Assessment - Yazid, Helmi; Wiyantoro, Lili Sugeng; Yan, Chen (International Journal of Supply Chain Management, 2020)
Abstract- The supply chain has major impact on the company's business strategy directly affecting its operational costs. Supply chain performances within the organization have a significant impact on the company's ability to provide services to their customers and create added value. Internal and external audit of the supply chain is one of the most powerful and fastest ways to reduce operational costs and provide the company competitive advantages in the global market in times of economic crisis. The purpose of this study is to identify the effect of opportunity, pressure, type of auditor and ability on fraud risk assessment in the perspective of internal auditors and external auditors at State Universities in Banten and Jakarta provinces, and to determine differences in perception Internal auditor with external auditor in fraud risk assessment at State Universities in Banten and Jakarta provinces. The population in this study is the internal auditor and external auditror of State Universities in Banten and Jakarta provinces. The research sample are 1) internal auditors of State Universities consisting of Internal Supervisory Unit auditors and auditors 2) external auditors of State Universities namely Auditors of Public Accountant Firms who have been auditors at State Universities in the provinces of Banten and Jakarta. The technique of determining the sample in this study was using purposive sampling technique. There are three colleges in Banten province that meet the criteria as a sample and three state universities in Jakarta 4. For internal auditors at universities it is assumed that the number of internal auditors at universities is assumed 15 auditors, thus the number of questionnaires distributed for internal auditor at State University in Banten and Jakarta provinces as many as 105 questionnaires (15 auditors x 7 state universities). Moreover, external auditors who have audited at the State University in Banten province 105 questionnaires follow the number of respondents in state university’s internal auditors. So that the number of questionnaires distributed in this study amounted to 210 questionnaires. The questionnaire was delivered directly to the respondent. The hypothesis testing using multiple linear regression and different tests with non-parametric test approach Mann-Whitney test. The results of this study are (1) there is a significant influence on opportunity, pressure, type of auditor and ability to assess fraud risk, (2) there is a difference in perception between internal auditors and external auditors in fraud risk assessment at State Universities in Jakarta and Banten.